A novel approach for assessing technical grade and quality of Lambda-cyhalothrin and acetamiprid in insecticides used in agricultural systems by HPLC technique in southern Benin - Tossou, E.; Tepa-Yotto, G.; Tchigossou, G.; Soglo, M.F.; Mbokou-Foukmeniok, S.; Bougna-Tchoumi, H.H.; Bokonon-Ganta, A.H.; Tamò, Manuele; Djouaka, R.F. (MDPI, 2023)
In Benin, synthetic insecticides are the main pest control option used by farmers to protect and enhance their production. However, failures to control the target pests are often observed after application and may be related to agricultural practices or insecticide quality. The present work was designed to assess a rapid, simple, and reliable analytical method for detecting and quantifying the most commonly used insecticides (λ-cyhalothrin and acetamiprid) in Benin. The analytical standard technical grade separation was performed by gradient reversed-phase high-performance liquid chromatography on a C18 stationary-phase column. The mobile phase consisted of a mixture of acetonitrile/water using a gradient flow. The flow rates were 1 and 1.4 mL·min−1 for λ-cyhalothrin and acetamiprid, respectively. The analysis times were 15 and 20 min, with retention times of 2.35 and 7.94 min for λ-cyhalothrin and acetamiprid, respectively. Results reveal that most of the surveyed farmers were not educated (70% < Primary School Certificate) and were men (95%). Of the main insecticides applied by farmers, λ-cyhalothrin and acetamiprid were found to be the most technical-grade ones. Furthermore, the analysis of insecticides showed that the concentrations obtained in our study often differed from the ones mentioned on insecticide labels. The proposed method is useful for quantifying insecticides in various technical and commercial formulations with little interference from additives.